Mastitis control in dairy herds - Blowey, R. W. (CABI, 2010)
This is the second edition of the book, containing 16 chapters which focus on prevention and control of mastitis as well as on the different factors that lead to mastitis resulting in poor milk quality. The book contains two appendices, the first contains a liner line chart and the second contains parlour audit. An index is also provided.